2014
DOI: 10.13058/raep.2014.v15n3.16
|View full text |Cite
|
Sign up to set email alerts
|

Análise Do Potencial E Perfil Empreendedor Do Estudante De Administração E O Ambiente Universitário: Reflexões Para Instituições De Ensino

Abstract: GUSTAVO HERMÍNIO SALATI MARCONDES DE MORAES fundação escola de comércio álvares penteado RESUMO A importância do empreendedorismo no Brasil aumentou significativamente nos últimos anos e os estudos atuais abordam o tema sob diversas perspectivas. O papel do jovem na criação de novos negócios já é uma realidade e a perspectiva é que se amplie nos próximos anos. Os incentivos ao empreendedorismo universitário podem ser observados de diversasensino e a aprendizagem, intra-empreendedorismo, influências do crescime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 0 publications
0
7
1
21
Order By: Relevance
“…A striking result concerns the lack of relevance identified in the variable "University Support." This vector is not associated with any of the entrepreneurial propensity functions to which it is assigned, an outcome which contrasts with earlier findings obtained by Iizuka and Moraes (2014), Moraes et al (2018) and Rocha and Freitas (2014). This suggests a lack of coordination and establishment of correct initiatives aiming at fostering entrepreneurial behavior in the Brazilian academia.…”
Section: Resultscontrasting
confidence: 88%
“…A striking result concerns the lack of relevance identified in the variable "University Support." This vector is not associated with any of the entrepreneurial propensity functions to which it is assigned, an outcome which contrasts with earlier findings obtained by Iizuka and Moraes (2014), Moraes et al (2018) and Rocha and Freitas (2014). This suggests a lack of coordination and establishment of correct initiatives aiming at fostering entrepreneurial behavior in the Brazilian academia.…”
Section: Resultscontrasting
confidence: 88%
“…Several studies have indicated that business education increases the positive perception about entrepreneurship, such as attitudes and intentions (Fayolle & Liñán, 2014;Iizuka & Moraes, 2014;Kolvereid & Moen, 1997;Liñán, Rodríguez-Cohard, & Rueda-Cantuche, 2011;Tkachev & Kolvereid, 1999). This importance is due to the fact that these perceptions precede entrepreneurial activities, such as past entrepreneurial exposure, context and institutions, and starting a new business (Fayolle & Liñán, 2014).…”
Section: University Environmentmentioning
confidence: 99%
“…In the field of research, undergraduate research projects, capstone course papers, and timely research that occur in different disciplines may focus on the theme of entrepreneurship (Fayolle & Liñán, 2014;Iizuka & Moraes, 2014).…”
Section: University Environmentmentioning
confidence: 99%
“…O estudo lançou luz para a necessidade de planejar, alinhar e direcionar a formação do jovem estudante administração quanto a sua formação humanística e profissional, estabelecendo aprendizado sobre a autoestima e autoconfiança aliada por aquisições de conhecimento de gestão comercial/empresarial. Outra pesquisa importante em relação a formação acadêmica do estudante de administração foi realizada por Iizuka (2014), porém, nesse caso, voltada para a importância do empreendedorismo nessa formação. Segundo esse autor a instituição de ensino não pode adotar uma única estratégia de ensino, pesquisa e extensão, pois os interesses e necessidades dos discentes captadas em sua pesquisa alternativas para estimular e concretizar o empreendedorismo, esses alunos continuariam a avaliar negativamente o ambiente universitário.…”
Section: Referencial Teóricounclassified